2014
DOI: 10.1371/journal.pone.0113676
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Literature and Evidence-Based Recommendations for Antibiotic Prophylaxis in Trauma: Results from an Italian Consensus of Experts

Abstract: BackgroundAntibiotic prophylaxis is frequently administered in severe trauma. However, the risk of selecting resistant bacteria, a major issue especially in critical care environments, has not been sufficiently investigated. The aim of the present study was to provide guidelines for antibiotic prophylaxis for four different trauma-related clinical conditions, taking into account the risks of antibiotic-resistant bacteria selection, thus innovating previous guidelines in the field.MethodsThe MEDLINE database wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 75 publications
(81 reference statements)
0
20
0
3
Order By: Relevance
“…Figures 3 and 4 illustrate higher use of several antibiotic agents (e.g., anti-pseudomonal PCN and carbapenems) and that multi-class exposure is common. Poole et al [41] highlight the risk of wound colonization with resistant bacteria in surgical patients after 48 hours of prophylactic antibiotic agents, likely a common circumstance in our patient population. In addition, an analysis of injured service members found that 14% of 2,079 trauma admissions were colonized with MDRGN bacilli at admission to participating hospitals in the United States, of which 98% received antibiotic agents before collection of surveillance swabs (£2 d of hospital admission).…”
Section: Discussionmentioning
confidence: 88%
“…Figures 3 and 4 illustrate higher use of several antibiotic agents (e.g., anti-pseudomonal PCN and carbapenems) and that multi-class exposure is common. Poole et al [41] highlight the risk of wound colonization with resistant bacteria in surgical patients after 48 hours of prophylactic antibiotic agents, likely a common circumstance in our patient population. In addition, an analysis of injured service members found that 14% of 2,079 trauma admissions were colonized with MDRGN bacilli at admission to participating hospitals in the United States, of which 98% received antibiotic agents before collection of surveillance swabs (£2 d of hospital admission).…”
Section: Discussionmentioning
confidence: 88%
“…La profilaxis se ha evaluado considerando las características diferenciales del trauma como lo son el tipo y lugar del trauma, exposición de masa encefálica, trauma penetrante, presencia de fístulas de LCR, fracturas de la base del cráneo o en comunicación con los senos paranasales (49,70,71) . En el metaanálisis realizado por Poole et al, se evaluó el uso de antibióticos profilácticos en fracturas de base de cráneo, estudio en el cual no se demostró beneficio aparente en la instauración de esta medida (71) .…”
Section: Profilaxis Antibiótica En El Trauma Craneoencefálicounclassified
“…Patients with penetrating abdominal trauma and concomitant thoracolumbar or sacral (TLS) fracture receiving prophylactic antibiotics for ≤ 48 hours do not develop spinal infections [29]. Prophylactic antibiotic research is applicable not only at the site of trauma wound infection but also in patients with nosocomial infections (early VAP and Clostridium difficile infection) [30, 31]. …”
Section: Introductionmentioning
confidence: 99%